Coherent synchronized oxidation reactions by hydrogen peroxide - Nagiev, T. M. (Tofik Murtuza ogly) (Elsevier, 2007)
Describes the relations between reactions in chemical and biochemical systems with special emphasis to high selective oxidation reactions by hydrogen peroxide. Outlines possible ways for the application of these reactions in an industrial scale. * Looking at new approaches to the synthesis and research of catalytic organic reactions by hydrogen peroxide * Discussing the important developments in the area of biomimetic catalysis * Covering biomimetic sensors, the new generation of analytical devices and their applications.